Design of Series-Fed, Single-Layer, and Wideband Millimeter-Wave Microstrip Arrays - Guo, Yu Qing; Pan, Yong Mei; Zheng, Shao Yong (IEEE transactions on antennas and propagation, 2020)
A series-fed millimeter-wave (mm-wave) microstrip linear array with single-layer structure and wide operating bandwidth is proposed and investigated. The antenna array simply consists of a microstrip line and a series of short stubs that are periodically introduced on one edge of the microstrip line, at an interval of about one guide wavelength. Owing to the perturbation of the additional stubs, the original symmetrical E-field distributions on the two opposite edges of the microstrip line become asymmetrical, and the intensities of the equivalent magnetic currents are unequal and unable to cancel each other out as in a pure microstrip line. As a result, the stub-loaded microstrip line can radiate effectively, producing broadside radiation patterns. The introduction of stubs can also generate an extra resonant mode, which combines with the resonant mode of the microstrip line, yielding a wide bandwidth of over 20%. In addition, the microstrip array is simply fed by a coaxial probe, without involving any complex feeding network. Therefore, the array configuration is very simple and compact. For demonstration, a 1 × 4\,\,1 -D microstrip linear array operating at 27 GHz is fabricated and tested. The measured results show that the array has an impedance bandwidth of 21.40%, an average realized gain of 12.18 dBi, and a first sidelobe level (FSLL) of about −13 dB. Moreover, the FSLL can be decreased to −28.4 dB by tapering the width of the microstrip line. Finally, the design is extended to realize a 4 × 4\,\,2 -D microstrip planar array. This planar array can achieve an impedance bandwidth of 19.15% and an enhanced gain of 18.30 dBi.